Loan Loss Provisions, Earnings Management, Capital Management, Cost Efficiency and Pro-cyclicality: The Japanese Experience - Liang, Siya (2017)
The focus of this paper is on the influences of loan loss provisioning in banks’ earnings and capital management and the pro-cyclicality behavior related to loan loss provisions. This paper tests these three hypotheses using a sample of 64 banks in Japan for the period 2010 to 2016. This paper incorporates econometric model with pooled time-series cross-sectional data, and tests relative significance of different variables affecting loan loss provisions behaviours of Japanese banks. There is strong statistical evidence of positive relationship between cost efficiency and loan loss provisions. In addition, cost efficiency is significantly affected by inflation rate and is robust for period 2010 to 2016.